Brain regions involved in ingestive behavior and related psychological constructs in people undergoing calorie restriction. (1st December 2016) - Kahathuduwa, Chanaka N.; Boyd, Lori A.; Davis, Tyler; O'Boyle, Michael; Binks, Martin
Abstract: Human food intake is regulated by physiological energy homeostatic mechanisms and hedonic mechanisms. These are affected by both very short-term and longer-term calorie restriction (CR). To date, there are parallel discussions in the literature that fail to integrate across these disciplines and topics. First, much of the available neuroimaging research focusses on specific functional paradigms (e.g. reward, energy homeostasis). These paradigms often fail to consider more complex and inclusive models that examine how potential brain regions of interest interact to influence ingestion. Second, the paradigms used focus primarily on short-term CR (fasting) which has limited generalizability to clinical application. Finally, the behavioral literature, while frequently examining longer-term CR and related psychological constructs in the context of weight management (e.g. hedonic restraint, 'liking', 'wanting' and food craving), fails to adequately tie these phenomena to underlying neural mechanisms. The result is a less than complete picture of the brain's role in the complexity of the human experience of ingestion. This disconnect highlights a major limitation in the CR literature, where attempts are persistently made to exert behavioral control over ingestion, without fully understanding the complex bio behavioral systems involved. In this review we attempt to summarize all potential brain regions important for human ingestion, present a broad conceptual overview of the brain's multifaceted role in ingestive behavior, the human (psychological) experiences related to ingestion and to examine how these factors differ according to three forms of CR. These include short-term fasting, extended CR, and restrained eating. We aim to bring together the neuroimaging literature with the behavioral literature within a conceptual framework that may inform future translational research.